Riqueza genérica y distribución de Elmidae (Insecta: Coleoptera, Byrrhoidea) en el departamento del Valle del Cauca, Colombia (2015)
Elmidae is a family of aquatic beetles common in clean water streams and widely used in studies of environmental bioindication. This work was proposed in order to recognize the richness of the Elmidae genera in the department of Valle del Cauca and recopile information about its distribution since biological colection data. A total of 3305 specimens (larvae and adults) were examined, mainly stored in the Museum of Entomology at the University of Valle and associated with field work completed between 1991 and 2014. The samples were collected from 116 locations within 19 municipalities, and are representative of 63 streams, mainly belonging to the Anchicayá, Cauca, Dagua and San Juan rivers basin and the Andean and Pacific natural regions. A total of 16 genera were documented: eleven Elminae (Austrolimnius, Cylloepus, Heterelmis, Huleechius, Macrelmis, Microcylloepus, Neoelmis, Notelmis, Onychelmis, Xenelmis and Stenhelmoides, the last not found in local collection) and five Larainae (Disersus, Hexanchorus, Phanocerus, Pharceonus and Pseudodisersus). These genera were distributed from 110 to 2440 m a.s.l., with greater taxonomic representation between 1000 and 2000 m a.s.l. The two genera most widely distributed were Macrelmis and Heterelmis, while the river with the highest taxonomic representation was Guabas. The distribution area for Austrolimnius, Huleechius, Notelmis and Xenelmis was expanded to the Valle del Cauca region.